Adenohypophyseal ascorbic acid: influences of oestradiol and methylene blue - Haluzík, M; Nedvídková, J; Schreiber, V (Physiological research, 1995)
The ascorbic acid (AA) concentration in anterior pituitary and blood plasma was measured by the Roe-Kuether method in control rats and rats treated with oestradiol benzoate alone, methylene blue alone and with both oestradiol and methylene blue. We have found that methylene blue alone caused a significant drop in hypophyseal both AA and plasma AA concentrations. Methylene blue treatment prevented the increase in plasma AA concentration in oestradiol benzoate-treated rats.
Keywords: Ascorbic Acid; methylenová modř; krysa rodu Rattus; Animals; mužské pohlaví; zvířata; osmolární koncentrace; adenohypofýza; Estradiol; Male; kyselina askorbová; Methylene Blue; Osmolar Concentration; Pituitary Gland, Anterior; Rats; Rats, Wistar; estradiol; potkani Wistar